Nerve conduction studies in early tuberculoid leprosy - Deepak Vashisht; Arjun Lal Das; Sanjeev S Vaishampayan; Surbhi Vashisht; Rajneesh Joshi (Wolters Kluwer Medknow Publications, 2014)
Context: Hansen's disease is a chronic illness; besides involving skin and peripheral nerves, it affects multiple organs. Nerve involvement is always present in leprosy, and it may be present much before the patient manifests clinically. Aims: To assess nerve conduction parameters in thickened and contralateral non-thickened nerves in early tuberculoid leprosy Materials and Methods: Fifty new untreated male patients with tuberculoid and borderline tuberculoid leprosy in the age group of 15-50 years with thickened peripheral nerves on one side were included in the study. Nerve conduction studies consisting of sensory and motor velocity (NCV), distal latencies, and amplitude were carried out on thickened ulnar, common peroneal, and posterior tibial nerves and contralateral normal nerves. Statistical Analysis Used: Mean values along with coefficient of variation were obtained for various parameters. These were compared with normal values of the control population. P value was used to verify statistical significance. Results: Nerve conduction parameters were deranged in most of the thickened nerves. Sensory parameters were affected early in the disease process. Conclusion: Additional parameters are required to assess nerve damage in early cases, where it is more in slow conducting fibers (average velocity fibers). Change in conduction velocity may not be marked; this calls for the measurement of fast fibers separately because potentials recorded are mainly from myelinated fibers.